Superior eyelid endoscopic transorbital approach to the tentorial area: A qualitative and quantitative anatomic study - De Rosa, Andrea; Di Somma, Alberto; Mosteiro, Alejandra; Ferrés, Abel; Reyes, Luis Alberto; Roldan, Pedro; Torné, Ramon; Torales, Jorge; Solari, Domenico; Cavallo, Luigi Maria; Enseñat, Joaquim; Prats-Galino, Alberto (Frontiers in Surgery, 2022)
Objective: Superior eyelid endoscopic transorbital approach (SETOA) is nowadays gaining progressive application in neurosurgical scenario. Both anatomic and clinical reports have demonstrated the possibility to take advantage of the orbital corridor as a minimally invasive route to reach anterior and middle cranial fossae and manage selected surgical lesions developing in these areas. The aim of our manuscript is to further shed light on other anatomic regions of the skull base as seen from a transorbital perspective, namely posterior cranial fossa and tentorial area, describing technical feasibility and steps in reaching this area through an extradural-transtentorial approach, and providing quantitative evaluations of the “working area” obtained through this route. Material and methods: 4 cadaveric heads (8 sides) were dissected at the Laboratory of Surgical Neuroanatomy (LSNA) of the University of Barcelona, Spain. A stepwise dissection of the transorbital approach to the tentorial area was described. Qualitative anatomical descriptions and quantitative analysis of working were evaluated by means of pre- and post-dissections CT and MRI scans and three-dimensional reconstructions were made by means of Amira®Software. Results: With the endoscopic transorbital approach, posterior cranial fossa dura was reached by means of an extradural middle cranial fossa approach and drilling of the petrous apex. After clipping of the superior petrosal sinus, tentorium was divided and cut. Endoscope was then introduced in the posterior cranial fossa, at the level of the tentorial incisura. Qualitative analysis provided description of the tentorial and petrosal surfaces of the cerebellum, middle tentorial incisura, cerebello-pontine fissures and, after arachnoid dissection, by means of a 30° endoscopic visualization, the posterior aspect of the cerebello-mesencephalic fissure. Quantitative analysis of the “working area” obtained after bone removal was also provided. Conclusions: This anatomic qualitative and quantitative study sheds light to the anatomy of the posterior cranial fossa contents, such as tentorial area and incisura, as seen through a transorbital perspective. First aim of our manuscript is to enrich the anatomical knowledge as seen through this relatively new corridor and to provide quantitative details and insights of technical feasibility inreaching these regions in a surgical scenario.